2022
DOI: 10.2186/jpr.jpr_d_21_00115
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of dental implant osseointegration by low-Intensity pulsed ultrasound: An <i>in vivo</i> preliminary study in a porcine model

Abstract: Purposes: Several studies have evaluated the interest of Low Intensity Pulsed Ultrasound (LIPUS) in the osseointegration of dental implants in murine or rabbit models. However, the thinness and narrowness bones make it difficult to study the effect of LIPUS. The purpose of this study is to assess the ability of LIPUS to stimulate bone formation in contact with a titanium dental implant in a porcine model. Methods: Eight adults mini-pigs were used. An implant is placed on each tibial crest in the metaphysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Notably, this ultrasound parameter not only harmless to the implant in vivo but as an FDA‐approved treatment, it has been proven to significantly increase bone formation and accelerate the healing process at the bone‐implant interface. [ 46 ] Histopathological sections of decalcified bone tissue were stained with H&E and evaluated for structural bone changes following bacterial infection using histological observations and histomorphometry analysis (Figure 6H). Severe bone destruction and chronic infection were observed in the Ti group.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this ultrasound parameter not only harmless to the implant in vivo but as an FDA‐approved treatment, it has been proven to significantly increase bone formation and accelerate the healing process at the bone‐implant interface. [ 46 ] Histopathological sections of decalcified bone tissue were stained with H&E and evaluated for structural bone changes following bacterial infection using histological observations and histomorphometry analysis (Figure 6H). Severe bone destruction and chronic infection were observed in the Ti group.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the maximal pull-out strength and stiffness were more preeminent on the side with LIPUS, which suggested that the combination of dental implants and bone is excellent [75]. Similarly, in the pig model, LIPUS can also promote bone formation and bone-implant contact surface healing [82]. Interestingly, a rat model was built with dental implants in the maxillary first molars extraction sockets successfully.…”
Section: Lipus Contributes To the Stability Of Implants Via Facilitat...mentioning
confidence: 94%
“…The included studies used mice (n=1), rats (n=5), rabbits (n=3), and pigs (n=1) as the implant animal models [10][11][12][13][14][16][17][18][19][20]. One study investigated implants in animals in which diabetes was induced by intraperitoneal injection of streptozotocin (STZ) [13].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…that LIPUS can shorten the overall treatment time [9]. In addition, studies have reported that LIPUS can promote the osteogenesis of dental implants [10][11][12]. However, in some studies, LIPUS has shown contrasting effects on dental implants [13,14].…”
Section: Introductionmentioning
confidence: 99%